High-throughput single-particle detections using a dual-height-channel-integrated pore. Issue 8 (25th March 2019) - Tonomura, Wataru; Tsutsui, Makusu; Arima, Akihide; Yokota, Kazumichi; Taniguchi, Masateru; Washio, Takashi; Kawai, Tomoji
Abstract : We report a proof-of-principle demonstration of particle concentration to achieve high-throughput resistive pulse detections of bacteria using a microfluidic-channel-integrated micropore. Abstract : We report a proof-of-principle demonstration of particle concentration to achieve high-throughput resistive pulse detections of bacteria using a microfluidic-channel-integrated micropore. We fabricated polymeric nanochannels to trap micrometer-sized bioparticles via a simple water pumping mechanism that allowed aggregation-free size-selective particle concentration with negligible loss. Single-bioparticle detections by ionic current measurements were then implemented through releasing and transporting the thus-collected analytes to the micropore. As a result, we attained two orders of magnitude enhancement in the detection throughput by virtue of an accumulation effect via hydrodynamic control. The device concept presented may be useful in developing nanopores and nanochannels for high-throughput single-particle and -molecule analyses.